Transformation and future trends of smart grid using machine and deep learning: a state-of-the-art review - Fahim, Khairul Eahsun; Islam, Md. Rakibul; Shihab, Nahid Ahmed; Rahman Olvi, Maria; Labib Al Jonayed, Khondaker; Das, Adri Shankar (International Journal of Applied Power Engineering (IJAPE), 2024)
A smart grid is a cutting-edge energy system designed to take over old-fashioned energy infrastructure in the twenty-first century. With comprehensive communication and computation capabilities, its primary objective is to increase energy distribution's dependability and efficiency while minimizing unfavorable effects. A number of approaches are needed for effective analysis and well-informed decision-making due to the massive infrastructure and integrated network of communications of the smart grid. In this study, we examine the architectural elements of the smart grid as well as the uses and methods using machine learning (ML) and deep learning (DL) with regard to the smart grid. We also clarify present research limitations and propose future directions for machine learning-driven data analytics. In order to improve the stability, reliability, security, efficiency, and responsiveness of the smart grid, this paper examines the implementation of several machine learning methodologies. This paper also covers some of the difficulties in putting machine learning solutions for smart grids into practice.